Croatian Vocational Schools Within a Museum-School Partnership - Zadravec, Valentina; Miklošević, Željka (Revija za elementarno izobraževanje, 2022)
The paper presents research on museum-school relationship from the point of view of teachers from secondary grammar and vocational schools. It explores their current and preferred interactions. The results show that teachers from vocational schools make field trips less frequently and are less satisfied with their relationship with museums. The characteristics of museum-school interactions are the same for both groups and form a model of low-intensity relations, with each institution maintaining its discrete authority, responsibilities and resources. Unlike the responses of the grammar-school teachers, those of vocational-school teachers do not indicate any development of the present relationship.
Keywords: Secondary grammar school, secondary vocational school, museums, museum-school partnership, models of interaction